Application of Galectin-3, HBME-1, Cytokeratin-19, and CD56 in the Diagnosis of Thyroid Neoplasm - Okdoo, Suren; Lkhagvadorj, Sayamaa; Malchinkhuu, Munkhzol; Baatarjalbuu, Nyamjargal; Bold-Erdene, Anarkhuu; Dargandorj, Tsolmonchimeg; Sharkhuu, Enkhtuya; Enkhbat, Bayarmaa (Central Asian Journal of Medical Sciences, 2019)
Objective: The purpose of this study was to investigate the effectiveness of immunohistochemical thyroid malignancy markers Galectin-3, HBME-1, Cytokeratin-19, and CD56 in the diagnosis of thyroid neoplasm. Methods: The study included a total of 53 cases of thyroid neoplasm on which immunohistochemical IHC staining was performed using the manual staining method. Results: The histopathological diagnosis of thyroid nodules was papillary thyroid carcinoma in 40 (75.5%), follicular thyroid carcinoma in 3 (5.7%), follicular adenoma in 8 (15.1%), medullary thyroid carcinoma in 1 (1.9%), and Hurthle cell carcinoma in 1 (1.9%). Out of 40 cases of papillary thyroid carcinoma, Galectin-3 and CK19 were positive in 36 (90%) cases while expression of HBME1 was seen in 32 (80%) papillary thyroid carcinoma cases, and 16 (40%) stained positive for CD56. For the three follicular thyroid carcinoma cases, CD56 was positive in one case, but the marker was positive in 7 out of 8 cases (87.5%) of follicular adenoma. Conclusion: Our results suggest Galectin-3 and HBME-1 are the most sensitive diagnostic markers for differentiating papillary carcinoma from follicular neoplasm.